2015
DOI: 10.1002/2015ja021221
|View full text |Cite
|
Sign up to set email alerts
|

Solar zenith angle‐dependent asymmetries in Venusian bow shock location revealed by Venus Express

Abstract: It has been long known that the Venusian bow shock (BS) location is asymmetric from the observations of the long‐lived Pioneer Venus Orbiter mission. The Venus Express (VEX) mission crossed BS near perpendicularly not only in the terminator region but also in the near‐subsolar and tail regions. Taking the advantage of VEX orbit geometry, we examined a large data set of BS crossings observed during the long‐lasting solar minimum between solar cycles 23 and 24 and found that the Venusian BS asymmetries exhibit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…The average B y is positive in the +E (+Z) hemisphere and negative in the −E hemisphere (Figures 5b and 5f ). This result that the B y direction correlating with the E hemisphere asymmetry was once obtained by Zhang et al [2010], Rong et al [2014], and Dubinin et al [2014a], and they suggested that dawnward magnetic field over north polar region is related with the E hemisphere asymmetry in the Venusian space environment caused by ion-pickup effect [Phillips et al, 1987;Chai et al, 2015]. Here our results show that besides the biased B y directions, the B z also has biased directions which are not related with the E hemisphere asymmetry.…”
Section: Global Looping Magnetic Field At Venussupporting
confidence: 71%
“…The average B y is positive in the +E (+Z) hemisphere and negative in the −E hemisphere (Figures 5b and 5f ). This result that the B y direction correlating with the E hemisphere asymmetry was once obtained by Zhang et al [2010], Rong et al [2014], and Dubinin et al [2014a], and they suggested that dawnward magnetic field over north polar region is related with the E hemisphere asymmetry in the Venusian space environment caused by ion-pickup effect [Phillips et al, 1987;Chai et al, 2015]. Here our results show that besides the biased B y directions, the B z also has biased directions which are not related with the E hemisphere asymmetry.…”
Section: Global Looping Magnetic Field At Venussupporting
confidence: 71%
“…An excess of pickup ions increases the size of the obstacle and causes the north-south asymmetry. It was recently demonstrated that the north-south asymmetry is larger for larger solar zenith angles but is observable even in the near-subsolar region (Chai et al 2015). The pole-equator asymmetry is however not observed in the subsolar region.…”
Section: Location and Structure Of The Bow Shockmentioning
confidence: 96%
“…However, the effect of pickup ions appears to be asymmetric. Near the terminator, pickup ions appear to play an important role, but in the near‐subsolar (35° < SZA < 75°) region their influence appears less important (Chai et al, ). The shocks observed by Balikhin et al () occur in the near‐subsolar region ( SZA = 67 − 68°), suggesting that pickup ions play a less important role in the observed shocks than would be the case at other locations.…”
Section: Introductionmentioning
confidence: 99%